2017
DOI: 10.1021/acs.jced.6b00769
|View full text |Cite
|
Sign up to set email alerts
|

Melting Behavior and Heat of Fusion of Compounds that Undergo Simultaneous Melting and Decomposition: An investigation with HMX

Abstract: Octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) undergoes almost a simultaneous transition from melting to decomposition, which makes direct measurement of the heat of fusion from calorimetric studies very difficult. The heat of fusion of HMX reported in the literature is unusually high when compared to those of energetic materials with similar molecular structures such as 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) and [3-nitrooxy-2,2-bis­(nitrooxymethyl)­propyl] nitrate. In this work, we investigate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…For gallic acid, two thermochemical transitions were reported, namely a solid–solid and solid–liquid thermochemical transitions [ 15 ]. In addition, various explosives have melted during decomposition, e.g., HMX (Octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) [ 16 ]. It is apparent that the vast majority of substances exhibiting a thermochemical transition are substances with the capability for increased hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…For gallic acid, two thermochemical transitions were reported, namely a solid–solid and solid–liquid thermochemical transitions [ 15 ]. In addition, various explosives have melted during decomposition, e.g., HMX (Octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) [ 16 ]. It is apparent that the vast majority of substances exhibiting a thermochemical transition are substances with the capability for increased hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been proposed that the formation of liquid state during a reaction of initially solid substances may result in increased reaction rates [ 10 ]. The Bawn model has been used for organic explosives [ 25 ] that exhibit such an effect, e.g., octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine [ 26 ], and have been reported to exhibit simultaneous decomposition and melting. Interestingly, the concept of Bawn kinetics has also been applied to pharmaceuticals [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMX is a rare compound that undergoes simultaneous melting and decomposition. Recent investigations of its melting properties with DSC by Bhattacharia et al 122 have revealed that at low heating rates of <5.5 °C/min, β-HMX does not melt but decomposes. At a 0.25 °C/min heating rate, the onset of decomposition is ∼237 °C, and at 6.0 °C/min, simultaneous decomposition and melting starts at ∼279 °C.…”
Section: Phase Transitions In Some Importantmentioning
confidence: 99%